Endoscopic ultrasound-guided radiofrequency ablation of pancreatic neuroendocrine tumors: a systematic review of the literature - Imperatore, Nicola (Endosc Int Open, 2020)
Background and study aims  Surgery is the mainstay therapy for pancreatic neuroendocrine tumors (P-NETs), but it is associated with significant adverse events (AEs). In recent years, endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) has been described for treating P-NETs. We performed a systematic literature review aimed at exploring the feasibility, effectiveness, and safety of EUS-RFA in treatment of P-NETs. Methods  The literature review was performed in PubMed/MEDLINE, EMBASE, and SCOPUS to identify all case reports of EUS-RFA for treatment of P-NETs. Results  Sixyt-one patients (males 49.2 %, mean age 64.5 years) and 73 tumors (mean size 16 mm, insulinomas 30.1 %) treated with EUS-RFA were included from 12 studies. The overall effectiveness of EUS-RFA was 96 % (75 % – 100 %) without differences between functional vs. non-functional P-NETs ( P  = 0.3) and without relevant issues about safety (mild AEs 13.7 %). While tumor location was not predictive for incomplete/non-response to EUS-RFA, greater tumor dimensions predicted treatment failure (21.8 ± 4.71 mm in the non-response group vs 15.07 ± 7.34 mm in the response group, P  = 0.048). At ROC analysis, a P-NET size cut-off value ≤18 mm predicted response to treatment, with a sensitivity of 80 % (95 % CI 28.4 % – 99.5 %), a specificity of 78.6 % (95 % CI 63.2 % – 89.7 %), a positive predictive value of 97.1 % (95 % CI 84.7 % – 99.9 %) and a negative predictive value of 30.8 % (95 % CI 9.1 % – 61.4 %), with an area under the curve of 0.81 (95 % CI 0.67 – 0.95). Conclusions  EUS-RFA is safe and effective for treating P-NETs. It may be reasonable to consider EUS-RFA for small P-NETs, irrespective of the functional status.